Generation of vector vortex pin-like beams and their propagation in turbulent atmosphere - Jia Li; Huijian Liang; Gaofeng Wu; Peipei Peng; Fei Wang; Yangjian Cai (APL Photonics)
Atmospheric turbulence consistently poses a significant challenge to the stable propagation of laser beams, particularly over long distances, as is often the case in free-space optical communication systems. To mitigate the adverse effects of atmospheric turbulence, there is a pressing need to develop specialized laser beams. In this study, we analyzed and derived the propagation characteristics of vector vortex pin beams (VVPBs) in free space and simulated their behavior under atmospheric turbulence using numerical methods. Our simulations demonstrate that, under identical conditions, VVPBs exhibit lower scintillation indices and beam wander compared to pin beams (PBs) over long distances. Furthermore, we experimentally generated VVPBs and PBs and measured their scintillation indices and beam wander as they traversed thermally induced turbulence in a laboratory setting. The experimental data corroborate our theoretical findings, confirming that VVPBs offer significant advantages in reducing the impact of turbulence. These findings could have substantial implications for the advancement of free-space optical communication and remote sensing technologies.